Face to the Village : the Riazan countryside under Soviet rule, 1921-1930 - McDonald, Tracy, 1966- (University of Toronto Press, 2011)
In the summer of 1924, the Bolshevik Party called on scholars, the police, the courts, and state officials to turn their attention to the villages of Russia. The subsequent campaign to 'face the countryside' generated a wealth of intelligence that fed into the regime's sense of alarmed conviction that the countryside was a space outside Bolshevik control. Richly rooted in archival sources, including local and central-level secret police reports, detailed cases of the local and provincial courts, government records, and newspaper reports, Face to the Village is a nuanced study of the everyday workings of the Russian village in the 1920s. Local-level officials emerge in Tracy McDonald's study as vital and pivotal historical actors, existing between the Party's expectations and peasant interests. McDonald's careful exposition of the relationships between the urban centre and the peasant countryside brings us closer to understanding the fateful decision to launch a frontal attack on the countryside in the fall of 1929 under the auspices of collectivization.